The example of a gender dialogue in British Poetry of late XVI and the 20th of XVII century - Сластьон, Сабріє Едемівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article is devoted to the analysis of a dialogue in two: gender and intertextual aspects. The examples of realization of three following functions of dialogue: communicative, informative and psychologic are highlighted in the poetry of the following poets of Elizabethan period and later the epoch of the King James I. The given analyses show not only the specific features of each very poet but also reveal the inner interaction of the poetic texts in their gender and motivic contexts. The differentiation method of motive and motivation concepts in poetic texts revealed not only explicit characters’ features and their time and place, but also highlighted more gender meanings.